Low Magnetic Field Detection Using a CuPt Nano Structure Made on a SiO2/Si Structure - Hassan Hajghassem; Seyedeh Maryam Banihashemian; Majidreza Aliahmadi (Sensors, 2009)
A Si/SiO2/CuPt structure is formed by depositing a very thin SiO2 layer between CuPt and P-type Si layers using e-beam evaporation. SEM images show the formation of CuPt nano clusters with an average size of less than 100 nm. This structure shows high sensitivity to applied magnetic fields at 77K and at low and high dc voltages such that magnetic field as low as 6 mT is detected using I-V and I-B measurements. The variation of current with various magnetic field strength at the constant voltage shows also an oscillatory behavior. The sensitivity of this structure to magnetic fields is believed to be due to small nano size of the platinum–copper structures as well as their discrete energy states and the tunneling of carriers into the insulating layer. Our results indicate that this structure may be a good candidate for small, simple, low cost and sensitive low magnetic field detectors.